ANALISIS HIRAULIKA TAMPUNGAN SUNGAI SESANIP KOTA TARAKAN SEBAGAI SUMBER CADANGAN AIR BAKU - Handayani, Rosmalia; Asta, Asta; Hakim, Hasyim Lukman (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
ABSTRACT: Tarakan is an area that does not have a source of raw water so that it uses rainfall for raw water needs for the population, and vice versa, when the city of Tarakan is subjected to heavy rain, it will experience flooding in several places with low elevation so that a long storage hydraulic study on the Sesanip River needs to be done. This study aims to examine the long storage hydraulics of the Sesanip River as a source of raw water reserves. Long storage is a water structure that is one of the efforts to accommodate and distribute domestic rainwater runoff with a large discharge. To conduct a study study on the long storage of the Sesanip River, the HEC-RAS program is needed so that it can model the flow front in the long storage, if there is a flood overflow that crosses the height limit of the cross section of the embankment, then redesign is done by excavating the soil and then reassessing it using HEC-RAS. so that the long storage section does not experience flood overflow From the results of a long storage study using a rational method for a 5-year return period, a discharge of 135,515 m3 / second was obtained, in the HEC-RAS program a simulation of water flow in a long storage length of 780 m with a total station of 156 sections of long storage occurred. flood outflow along 200 m from upstream to mid-downstream with many stations, namely 56 long storagesections.Keywords: Long Storage, Raw Water, Hydraulics, Rational Methods, Simulation, Cross-section, HEC-RAS, Discharge ABSTRAK: Tarakan merupakan daerah yang tidak memiliki sumber air baku sehingga memanfaatkan curah hujan untuk kebutuhan air baku bagi penduduk, dan sebaliknya Kota Tarakan ketika diguyur hujan yang deras akan mengalami banjir di beberapa tempat yang elevasi datarannya rendah sehingga studi kajian hidraulika long storage pada Sungai Sesanip perlu dilakukan.Penelitian ini bertujuan untuk mengkaji hidraulika long storage Sungai Sesanip sebagai sumber cadangan air baku. Long storage merupakan bangunan air yang menjadi salah satu upaya untuk menampung serta ,menyalurkan limpasan air hujan domestik dengan debit yang besar. Untuk melakukan kajian studi pada long storage Sungai Sesanip diperlukan program HEC-RAS agar dapat memodelkan muka aliran pada long storage, jika terjadi luapan banjir yang melewati batas ketinggian tanggul penampang, maka dilakukan desain ulang dengan pekerjaan galian tanah kemudian di kaji lkembali menggunakan HEC-RAS hingga penampang long storage tidak mengalami luapan banjir.Dari hasil kajian long storage menggunakan metode rasional untuk periode kala ulang 5 tahun di dapatkan debit sebesar 135.515 m3/detik, pada program HEC-RAS dilakukan simulasi aliran air pada long storage sepanjang 780 m dengan dengan total stasiun sebanyak 156 penampang long storage, dan terjadi luapan banjir sepanjang 200 m dari titik hulu menuju pertengahan hilir dengan banyak stasiun yaitu 56 penampang long storage.Kata Kunci: Long Storage, Air Baku, Hidraulika, Metode Rasional, Simulasi, Penampang, HEC-RAS, Debit